The Role of Madrasah Supervisors in Implementing Parent Classes as Part of EDRA to Strengthen Parent–Teacher Collaboration at RA As Sholihat Cangkringturi - Wulyaningsih, Nani (Indonesian Journal of Teaching and Learning, 2025)
Purpose – This study aims to examine the effectiveness of Parent Class/Parenting programs as part of the supervisory assistance and the implementation of the Roudlotul Athfal Self-Evaluation (EDRA) system in improving parent–teacher collaboration at RA As Sholihat Cangkringturi, Prambon District, in 2025. Methodology – This research employed a qualitative descriptive design with observation and documentation as the primary data collection techniques. The subjects included teachers, students, and parents of RA As Sholihat. Data were analyzed using a flow model consisting of data reduction, data display, and conclusion drawing. The supervisory intervention introduced the EDRA self-evaluation application to help identify weaknesses, needs, and potential within the institution, followed by mentoring sessions and the implementation of Parent Class activities. Findings – Initial observations revealed limited understanding among teachers and school leaders regarding essential documents such as RKT, RKRA, RKJM, and the curriculum, with many relying on copied templates without understanding their substance. Through EDRA-based supervision and the implementation of Parent Class activities, the institution successfully identified root problems and improvement strategies. By the second cycle, parent involvement and communication with teachers increased significantly, indicating a positive impact of the parenting program on strengthening collaboration. Novelty – This study highlights the emerging role of madrasah supervisors as educational companions in line with the new national supervisory framework, demonstrating how EDRA-based mentoring combined with Parent Class implementation can effectively. Significance – The findings provide practical insights for madrasah supervisors, school leaders, and early childhood educators on optimizing supervision practicesto support learning in early childhood education settings.